In Search of a Soft Landing: How Premigration Work Attainments Influence Identity Transformation Processes of Refugee Entrepreneurs - Amin, Joris; van Burg, Elco; Stam, Wouter (Organization Science, 2025)
Highly educated refugees who have been uprooted from their country of origin often struggle to secure employment that matches their abilities. Overcoming this sudden loss of achieved work identity is crucial for refugees’ future well-being and integration in the host country. In this study, we identify the behavioral and cognitive practices used by highly educated refugee entrepreneurs to resolve the incongruence between their selves and the host country environment and delineate core conditions that explain why only some complete these identity transformations successfully. Based on an in-depth ethnography at an incubator designed for refugees with entrepreneurial ambitions, we develop theory about how and when highly educated refugees’ past identities enable or constrain their ability to create new work identities in alignment with the new environment. Our findings reveal the critical role played by identity flexibility and a refugee’s attributions of premigration work attainments in this process. Surprisingly, we find that those who attribute prior career accomplishments internally—and are, thus, driven by self-perceptions of being resourceful and adaptive in the past—exhibit only limited identity flexibility. As a result, they struggle the most with reconstructing their identity in ways that aid their integration in the host country. History: This paper has been accepted for the Organization Science Special Issue on Migration & Organizations.